The role of information in a lifetime process - a model of weight maintenance by women over long time periods - Judit Bar-Ilan; Nira Shalom; Snunith Shoham; Shifra Baruchson-Arbib; Irith Getz (Information Research: An International Electronic Journal)
Introduction. This paper proposes a model of information behaviour of women during their life-long struggle to maintain normal weight. Method. The model is integrative and contextual, built on existing models in information science and several other disciplines, and the life stories of about fifty Israeli women aged 25-55 and interviews with professionals. Analysis. The life stories of the participating women were analyzed qualitatively, major themes and phases were identified. Results. Weight loss and/or maintenance behaviour is a lifetime process in which distinctive stages were identified. In most cases the weight gain - weight loss - maintenance cycle is a recurring cycle. Information is a major resource during the process: several roles of information were defined: enabling, motivating, reinforcing, providing background information related to weight problems and creating the internal cognitive schema related to food and weight. Information behaviour and the roles of information vary with the different stages. Information needs are also influenced by the specific stage of the process. Information gathered at previous cycles is reused, and information gained through previous experience effects behaviour in the current cycle. Conclusion. The model has both theoretical and practical implications.